Project-Based Learning in Science Education: Strategies for Fostering Environmental Awareness in Fifth-Grade Students at SDIT Wihdatul Ummah Makassar - Nurlina Nurlina; Erma Suryani Sahabuddin; Muhammad Faisal (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study examines the application of the Project-Based Learning (PjBL) model in Natural and Social Sciences education to enhance environmental awareness among fifth-grade students at SDIT Wihdatul Ummah in Makassar City. The background of this research stems from the low environmental awareness observed among students, evidenced by behaviors such as littering, lack of concern for energy conservation, and minimal participation in school cleanliness activities. The study aimed to improve students' environmental consciousness by implementing the PjBL model, where students were tasked with creating environmental awareness posters. The research used a Classroom Action Research (CAR) method, which was carried out in two cycles, each consisting of three meetings. The stages of PjBL involved determining essential questions, project planning, scheduling, project implementation, result testing, and evaluation of experiences. Data collection was done through observations, attitude questionnaires, and documentation of student activities. The findings showed that the PjBL model successfully increased students' active participation, creativity in expressing environmental awareness through posters, and their practical actions toward environmental protection. The environmental awareness indicators, such as maintaining cleanliness, managing waste, conserving energy, understanding waste disposal systems, and using cleaning tools, significantly improved from Cycle I to Cycle II. The results indicate that the PjBL model is effective in enhancing environmental awareness while making the learning process more engaging and contextual for elementary school students.